RESPONSE OF POTATO TO PHOSPHORUS AND PHOSPHORUS SOLUBILIZING BACTERIA IN BROWN HILL SOILS OF SHIMLA - Sud, K C.; Jatav, M. K. (Potato Journal, 2013)
A study was conducted on acidic soil with high availability of phosphorus to know the role of phosphorus (P) and phosphorus solubilizing bacteria (PSB) on P use efficiency by the potato crop under rainfed conditions. A significant response to P application as well as PSB applied through seed tuber inoculation was observed. Their combined application resulted in higher yield of medium sized tubers, total tuber yield and also nutrients uptake. Phosphorus recovery was also higher by over 14% in combined application of PSB and P than that of application of P alone.